Altered hemostatic balance in favor of a procoagulant state in pregnant women with systemic lupus erythematosus - Antovic, Aleksandra; Lini, Daniele; Soutari, Nida; Lalic-Cosic, Sanja; Zickert, Agneta; Mc Nicholas, Andrea; Bremme, Katarina; Sennström, Maria; Franceschini, Franco; Svenungsson, Elisabet; Andreoli, Laura; Gunnarsson, Iva (Frontiers in Lupus, 2025)
Objectives This study aimed to investigate hemostatic parameters in pregnant patients with systemic lupus erythematosus (SLE) in relation to the use of antithrombotic prophylaxis, preeclampsia (PE), and antiphospholipid antibody status. Patients and methods In total, 34 pregnant patients with SLE and 80 pregnant healthy controls (HC) without PE were included. Patients with SLE were sampled during the first and third trimester of gestation. We analyzed fibrinogen, D-dimer, and global hemostatic parameters including the overall coagulation potential (OCP), overall hemostatic potential (OHP), and the overall fibrinolysis potential (OFP). Fibrin structure was visualized using scanning electron microscopy. Results The median age of the patients with SLE was 33 (range 23–42) years and 31 (26–38) years in the HC. The median disease duration was 10 (range 0–26) years. All but two patients with SLE received prophylaxis with low-dose acetylsalicylic acid (LDASA) and 11 received low-molecular-weight heparin (LMWH). OCP and OHP were significantly increased in the patients with SLE compared to HC (p < 0.01). The levels of fibrinogen and D-dimer increased throughout the pregnancies in the patients with SLE, but no differences were found in the third trimester compared to controls. Among the patients treated with LMWH, OCP, OHP, and OFP were undetectable in two, both of whom were on high prophylactic dosage, and one developed PE. OCP, OHP, and OFP levels were not affected by low prophylactic doses of LMWH. Despite LDASA, preeclampsia occurred in four patients with SLE (12.5%); of whom two received a high prophylactic LMWH dose. Five of 32 (15.6%) patients had major bleeding complications at delivery. There were no thromboembolic complications. Conclusions In this pilot study, pregnant patients with SLE developed a hypercoagulable state throughout pregnancy, as demonstrated by the global hemostatic parameters OCP and OHP, except for two patients who were treated with a full dosage of LMWH. The alterations in the coagulation system in SLE pregnancy need to be further studied with the aim of optimizing treatment strategies.